2014
DOI: 10.1016/j.procbio.2014.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Sludge bulking impact on relevant bacterial populations in a full-scale municipal wastewater treatment plant

Abstract: a b s t r a c tWe have investigated the changes of microbial community structures and the concomitant performance in two biological wastewater treatment systems (conventional and inverted A 2 /O processes) over a whole cycle of sludge bulking. A low level of filament abundance was observed during non-bulking period, with types 0092 and 0041 as the dominant filamentous bacteria. With the increase of the sludge volume index values from 76 (73) to 275 (300) mg/L, the filament abundance estimated by microscopic ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
30
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 29 publications
(37 reference statements)
5
30
0
Order By: Relevance
“…Proteobacteria, Actinobacteria, Chloroflexi, Firmicutes, and Bacteroidetes were found in the 3 types of typical AS samples, and their abundances changed considerably with the occurrence of sludge bulking. Similar to a previous study on the bacterial community structure of AS samples from a bulking municipal WWTP in northern China using a cloning method (Wang et al, 2014), our present study showed that sludge bulking resulted in a significant shift in bacterial compositions from a dominance of Proteobacteria to a dominance of Actinobacteria. Yet another study on seasonal microbial variations of AS from a full-scale WWTP over 4 years using metagenomic analysis showed Proteobacteria to be the predominant phylum in winter and summer samples and Actinobacteria to be usually higher in winter than in summer (Ju et al, 2014).…”
Section: Dynamics Of Bacterial Communities During Sludge Bulkingsupporting
confidence: 89%
See 4 more Smart Citations
“…Proteobacteria, Actinobacteria, Chloroflexi, Firmicutes, and Bacteroidetes were found in the 3 types of typical AS samples, and their abundances changed considerably with the occurrence of sludge bulking. Similar to a previous study on the bacterial community structure of AS samples from a bulking municipal WWTP in northern China using a cloning method (Wang et al, 2014), our present study showed that sludge bulking resulted in a significant shift in bacterial compositions from a dominance of Proteobacteria to a dominance of Actinobacteria. Yet another study on seasonal microbial variations of AS from a full-scale WWTP over 4 years using metagenomic analysis showed Proteobacteria to be the predominant phylum in winter and summer samples and Actinobacteria to be usually higher in winter than in summer (Ju et al, 2014).…”
Section: Dynamics Of Bacterial Communities During Sludge Bulkingsupporting
confidence: 89%
“…When sludge bulking occurs, the overgrowth of filamentous bacteria could result in a decrease in non-filamentous bacteria, making these non-filamentous bacteria susceptible to being washed out from WWTPs (Wang et al, 2014). Similar to the report of Wang et al (2014), our 454 pyrosequencing results indicated that sludge bulking resulted in a significant shift in Proteobacteria compositions from a dominance of Betaproteobacteria to that of Alphaproteobacteria. A detailed analysis showed that the abundance of Alphaproteobacteria increased considerably with the occurrence of sludge bulking because of the increase in some functional bacteria such as Rhodobacter (Kong et al, 2007), whereas the abundance of Betaproteobacteria decreased markedly with the occurrence of sludge bulking due to the decrease in certain functional bacteria such as Thauera, Dechloromonas, Zoogloea, and Nitrosomonas (Wang et al, 2014).…”
Section: Dynamics Of Bacterial Communities During Sludge Bulkingsupporting
confidence: 80%
See 3 more Smart Citations